Goddess figure on the niche of the moulding of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
This is a devakoshtha (niche) on the surface of the kumbha (pot-shaped) moulding, which is part of the high plinth of the Chaunsath Yogini Temple. Each of these devakoshthas is formed of two slender pilasters with a ghatapallava (vase and foliage) motif. The niche is crowned by a gavaksha (dormer window) design. Most of the sculptures from the devakoshtha are lost, but the few sculptures that survive are of goddesses. The presence of these goddesses supports the Shakta affiliation of the temple.